Giant Medial Sphenoid Wing Meningioma with Hyperostosis Sphenoid Bone : A Case Report - Faisal,; Hutagalung, Tommy Rizky; Dharmajaya, Ridha (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2020)
Introduction: Meningiomas of the sphenoid wing make up approximately 15“20% of total cranial meningiomas. Giant medial sphenoid involve the dura of the greater and lesser wings of the sphenoid, the anterior clinoid process, the spheno-orbital bone and the middle cranial fossa, hyperostosis bone was common to found. Surgical management of giant medial sphenoid is extremely challenging due to their intimate relationship with vital neural structures. Case Report : A 40-year-old woman came to the emergency room with complaints of decreased consciousness that had been experienced since 1 week , recurrent headaches, weakness of the right limb and history of blurred vision. A non-contrast head ct scan and MRI brain contrast revealed an extra-axial giant mass meningioma in left medial sphenoid wing with hyperostosis bone Craniectomy tumor removal was performed with a subtemporal approach combined with cranio-orbytozygotomy. Discussion : Hyperostosis is a common phenomenon occuring in different meningiomas with incidence ranging from 25 to 49% of meningiomas.it is most commonly seen in sphenoid wing and convexity meningioma . The bony hyperostosis is of neoplastic nature and is responsible for many of the clinical manifestation of such tumors and hence should be totally drilled to achieve cure and avoid recurrence. Conclusion : Sphenoid wing meningioma en plaque, mainly meningothelial meningiomas, are characterized by the associated bony hyperostosis that gives them a distinct radiological appearance. Extensive tumor removal is crucial for correction of proptosis and adequate visual decompression to achieve satisfactory cosmetic and functional outcome.